Light Chain Amyloidosis: Epidemiology, Staging, and Prognostication - Kelty R. Baker (Methodist DeBakey Cardiovascular Journal)
Amyloidosis is a disorder of protein misfolding and metabolism in which insoluble fibrils are deposited in various tissues, causing organ dysfunction and eventually death. Out of the 60-plus heterogeneous amyloidogenic proteins that have been identified, approximately 30 are associated with human disease. The unifying feature of these proteins is their tendency to form beta-pleated sheets aligned in an antiparallel fashion. These sheets then form rigid, nonbranching fibrils that resist proteolysis, causing mechanical disruption and local oxidative stress in affected organs such as the heart, liver, kidneys, nervous system, and gastrointestinal tract. Here we review the epidemiology of light chain amyloidosis, the staging, and the concomitant prognostication that is critical in determining the appropriate treatment.